On the Optimal Spatial Resolution of Crustal Mass Distributions for Forward Gravity Field Modelling - Kuhn, Michael; Featherstone, Will (Ziti Editions, 2003)
The primary drawback of forward gravity field modelling is that the Earth's density distribution must be known. Nowadays, increasingly more information on the Earth?s mass distribution is available, such as high-resolution digital elevation models, models of the crustal mass distribution as well as of deeper masses. This paper studies the spatial resolution of crustal mass distributions required in forward gravity field modelling using spherical harmonic expansion of global data and power spectral density functions of local data. The spectral sensitivity of different gravity field parameter is examined by means of degree variances and analytical degree variances. Numerical results for the geoid height and gravity disturbance are given globally and in a test area over part of Australia.